Peran Edukasi Badan Usaha Milik Desa (BUM Desa) Dalam Pemberdayaan Masyarakat Melalui Usaha Peternakan - Zadmoko, Dwi; Wijaya, Mahendra; Widiyanto, Widiyanto (Jurnal Ilmiah Global Education, 2024)
This research examines the educational role of Village-Owned Enterprises (BUM Desa) in empowering communities through livestock activities. Case study in Ngrancang Village, Tambakrejo District, Bojonegoro Regency. The research location was chosen because the majority of the people are farmers. The aim of the research is to examine the educational role carried out by BUM Desa in livestock businesses to provide benefits to the community in the social and economic fields at the local village level. Data from the Ministry of Villages PDTT for 2023 explains that in Tambakrejo District there are 18 BUM Villages with BUM Village status, including: 7 villages with pioneer status, 2 villages with beginner status, 9 villages with developing status and not yet advanced status. , where the Village BUM in Ngrancang Village is included in the village with developing status. This research uses qualitative methods with observation, in-depth interviews, and documentation. BUM Desa was chosen as the driving force for the development of the local village economy and the main actor in managing livestock businesses in collaboration with the community. The role of village BUM education includes livestock management, animal care, natural resource management, and marketing of livestock products. The research results show that through education, BUM Desa has succeeded in increasing community productivity and income in the livestock sector. This research also identifies the challenges faced, such as limited business capital and human resources needed to increase the effectiveness of BUM Desa in livestock businesses.